(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2024)
Phacoemulsification with PCIOL implantation is the method of choice for the removal of a cataractous lens. After the surgery, patients are advised to perform salat without sajdah. In this study, we aimed to evaluate the influence of sajdah in praying salat. One hundred patients who performed salat with sajdah from the day of phacoemulsification cataract surgery were randomly selected for group A, and 100 patients who performed salat without sajdah were selected for group B. Visual acuity, IOP, and central corneal thickness were measured, and iris prolapse, subconjunctival hemorrhage, and patient compliance were compared on the 1st POD, after 1 week, and after 1 month. There was no significant difference in visual acuity, IOP changes, central corneal thickness, subconjunctival hemorrhage, or iris prolapse between group A and group B. However, patient satisfaction was significantly higher in group A when praying salat with sajdah. This study suggested that there was no hazard associated with sajdah or downward bending after phacoemulsification surgery and that there might be no restriction on forward bending, downward bending, or sajdah from the day of phacoemulsification cataract surgery. Bangabandhu Sheikh Mujib Med. Coll. J. 2024;3(2):97-100